The Impact of COVID-19 Pandemic on the Engineers' Performance - AL-KAFF, OMAR YAHYA MOHAMMED (İstanbul Kültür Üniversitesi, 2022)
During COVID-19 crisis, numerous studies have investigated employee's performance as a major determinant factor of organizational success. In such hard times, there was no noticeable focus on engineers' performance despite their critical roles and increased responsibilities. Thus, this research is initiated to study the impact of COVID-19 pandemic on engineers' performance. Survey data from 100 engineers have been analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM), also reliability and validity of the constructed model have been ensured using a recently proposed new Confirmatory Composite Analysis method (HCCA). Path model results suggest a total positive impact of COVID-19 pandemic on engineers' performance through Organizational Change, Work-Life Balance, Job Satisfaction and Stress as mediators. The level of their experienced stress has been found to increase the performance rather than the opposite, which probably indicates successful management implementations that enabled creating performance improvements even amid the catastrophe. Control variables of Gender, Work Experience, Responsibility of Children, and Marital Status are additionally examined, and more experienced and non-married engineers have been observed to have relatively increased performance than others.
COVID-19 Pandemisinin Mühendislerin Performansı Üzerindeki Etkileri
▪ Yüksek lisans tezi.
Keywords: COVID-19; Engineers’ Performance; Partial Least Square Structural Equation Modeling (PLS-SEM); Hair’s Confirmatory Composite Analysis (HCCA)